The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Advances in Innovative Engineering and Technologies 2015
DOI: 10.18797/caasr/iciet/2015/11/27/08
|View full text |Cite
|
Sign up to set email alerts
|

Mining Data-Logs From Intelligent Tutors to Create Learning Profiles of Students

Abstract: Intelligent tutoring systems are being used to teach mathematics due to the fact that they can provide individual tutoring, instant feedback on learning and flexibility to learn at own pace. In such computer supported learning environments, it is necessary that students develop the ability to learn independently. This paper reports the result obtained after mining the data logs generated by the intelligent tutoring system, ALEKS. Three clusters were generated after using two-step cluster analysis based on a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This ratio is represented by the variable mtop (which is an abbreviation of mastered_to_practiced). It was found that there is a moderately strong, positive and significant correlation between the value of mtop and student's final exam marks (r=0.466, sig=0.0) [10]. A high value of this variable indicates that a student is able to master most of the topics she is attempting to master, whereas a low value indicates contrary.…”
Section: Research Context and Methodologymentioning
confidence: 98%
See 4 more Smart Citations
“…This ratio is represented by the variable mtop (which is an abbreviation of mastered_to_practiced). It was found that there is a moderately strong, positive and significant correlation between the value of mtop and student's final exam marks (r=0.466, sig=0.0) [10]. A high value of this variable indicates that a student is able to master most of the topics she is attempting to master, whereas a low value indicates contrary.…”
Section: Research Context and Methodologymentioning
confidence: 98%
“…The objective of learning analytics is to derive information which can reveal how students use the intelligent tutoring or other e-learning systems and identify potential determinants of academic achievement. [17,20,10].Application of methods of learning analytics can be a powerful means to inform and support learners, teachers and their institutions in better understanding and predicting personal learning needs and performance [20,44]. This analysis can reveal detailed information about different patterns of learning activities, such as the rate at which learner is progressing in the learning environment, under which circumstances their progress is accelerated or decelerated.…”
Section: 3learning Analyticsmentioning
confidence: 99%
See 3 more Smart Citations